TaRar1 Is Involved in Wheat Defense against Stripe Rust Pathogen Mediated by YrSu - Wang, Xiaojing; Wang, Yaru; Liu, Peng; Ding, Yan; Mu, Xiaoqian; Liu, Xiping; Wang, Xiaojie; Zhao, Mengxin; Huai, Baoyu; Huang, Li; Kang, Zhensheng (Frontiers in Plant Science, 2017)
RAR1 is a eukaryotic zinc-binding protein first identified as required for race-specific resistance to powdery mildew in barley. To study the function of TaRAR1 involvement in wheat (Triticum aestivum L.) defense against the infection of stripe rust pathogen Puccinia striiformis f. sp. tritici (Pst), we identified and cloned three wheat homeologous genes highly similar to the barley HvRar1, designated as TaRar1-2A, TaRar1-2B, and TaRar1-2D. The three TaRAR1 proteins all contain two conserved cysteine-and histidine-rich domains (CHORD-I and -II) shared by known RAR1-like proteins. Characterization of TaRar1 expression revealed that the expression was tissue-specific and up-regulated in wheat during stripe rust infection. Moreover, the transcription of TaRar1 was induced by methyl jasmonate, ethylene, and abscisic acid hormones. The same results were observed with drought and wound treatments. After TaRar1 was silenced in wheat cultivar Suwon11 containing the stripe rust resistance gene YrSu, the endogenous salicylic acid (SA) level, the hydrogen peroxide (H2O2) accumulation and the degree of hypersensitive response (HR) were significantly decreased, and the resistance to the avirulent pathotype of stripe rust was compromised. Meanwhile, the expression of catalase, an enzyme required for H2O2-scavenging, was up-regulated. Taken together, we concluded that TaRar1 is involved in wheat defense against stripe rust mediated by YrSu, and the defense was through SA to influence reactive oxygen species accumulation and HR.